An open-source tool for visualization of climate mitigation scenarios: Mipplot. (May 2021) - Ju, Yiyi; Sugiyama, Masahiro; Silva Herran, Diego; Wang, Jiayang; Inoue, Akimitsu
Abstract: Synthesizing and communicating knowledge on climate change to policymakers and stakeholders is often difficult due to the complexity and diversity of underlying research. As a "translation" instrument, we present the mipplot tool, an open-source R package that can be used to visualize data of long-term climate mitigation scenarios. With simple commands and under a user-friendly language platform, this tool generates plots in multiple languages for any scenario dataset following the data submission format of the Integrated Assessment Modeling Consortium. The plots can be generated both by function call in R environment and by an interactive interface in a web browser environment, which offers greater flexibility of inputs and suits both experts and non-experts. Moreover, its capability of specifying aggregation rules and different display languages extends its applicability to a broader range of users. Highlights: An open-source R package mipplot is presented to visualize the data of long-term climate mitigation scenarios. It is enhanced in the flexible usability by function calls and interactive interface. It includes multi-language outputs. Via mipplot, both expert and non-expert users can access the research outcomes from IAM climate mitigation scenarios.